Effect of Seed Disinfectants on in vitro Seed Germination and Seedling Development in Eggplant - M Kaur (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2014)
The present investigation reports effects of disinfectants on culture contamination, seed germination and seedling growth in eggplant. Mercuric chloride hampers seed germination when seeds are treated with 0.1% solution above 2 min duration and lesser durations are not helpful in controlling in vitro contamination. The highest seed germination (89.97%) was recorded with 50% commercial bleach for 20 min in the genotype BL-3, followed by BR-16 (88.53%), BR-14 (86.19%), BL-5 (86.16%) and BSR-23 (85.57%). However, least number of seeds germinated in BR-18 (10.94%), BSR-25 (13.27%) and BL-7 (18.62%) when disinfected with 75% commercial bleach for 25min. Overall results revealed that 50% commercial bleach concentration (73.76%) was better than 75% (36.85%), and 20 min duration (60.82%) was better than 25 min (49.80%) for seed disinfection. Among the varieties, BL-3 was at the top (68.85%) and BR-18 at the lowest (34.16%) edge for per cent seed germination. Seedling growth (cm) with use of commercial bleach was quite satisfactory compared to disinfection with HgCl2, where, 50% commercial bleach favored a good stand of plant lets even after 10 days, showing a healthy root (3cm), hypocotyl (5cm) and cotyledons (1.5cm).